Desafios da alfabetização científica : uma proposta de formação continuada com professores dos anos iniciais do ensino fundamental - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
The proposed work, entitled "Challenges of Scientific Literacy: A Proposal for Ongoing Education with Elementary School Teachers," highlights significant contributions, including the recognition of challenges in scientific literacy, the emphasis on ongoing teacher education to improve teaching practices, the appreciation of the school's integral role in students' education, the adaptation of teaching to the students' context, and the use of interdisciplinary didactic sequences. However, effective implementation, local adaptation, impact assessment, access to resources, and the context of Brazilian education represent critical challenges to be considered. Science education has, as one of its objectives, the development of scientific literacy. However, teachers don't always manage to achieve this goal, and the content is approached in a uncritical, decontextualized, and fragmented manner. It's essential for the Science teacher to have the opportunity to create and develop teaching strategies aimed at improving their practice in Science Education or Scientific Literacy. Therefore, considering this pedagogical challenge, the importance of ongoing education also emerges as a critical and reflective process, and the school, in this regard, plays a fundamental role in the holistic development of the individual. Through courses, activities, and projects offered to teachers, reflection on the need to understand and adjust their practice with future obstacles that may arise can take place. Scientific literacy, therefore, in the pedagogical practice of Science Education, needs to acquire new meanings and provide students with an expansion of their knowledge and an understanding of their role in society. The objective of this work was to investigate how a proposal for ongoing education for teachers of early years in Elementary School could contribute to the appropriation of meanings regarding scientific literacy. The methodological procedure adopted was qualitative-quantitative in a field research, through participant observation. The research was carried out with five teachers from the 1st, 4th, and 5th grades of the Rita Mônica Lêdo Municipal School, located in Rianápolis-Goiás. The Educational Product is an In-Service Ongoing Education Course, using interdisciplinary didactic sequences as a didactic strategy, structured in Three Pedagogical Moments (Initial Problematic Situation, Knowledge Organization, and Application of Knowledge) and based on the three structuring axes for the promotion of Scientific Literacy in the early years of Elementary School. It is expected that this research, as well as the educational product, can significantly contribute to Teachers' Education, leading them to a critical reflection on their practice, in order to optimize their classes with the acquired knowledge and adjust teaching to the reality of students.
Challenges of scientific literacy : a proposal for continuing training with teachers in the early years of elementary school
Keywords: Alfabetização Científica; Ensino de Ciências; Estratégias didáticas; Formação docente; Scientific literacy; Science teaching; Didactic strategies; Teacher training; CIENCIAS HUMANAS::EDUCACAO; EDUCACAO::ENSINO-APRENDIZAGEM